2011
DOI: 10.1186/1477-5956-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the complexities of the wheat flour proteome using quantitative two-dimensional electrophoresis, three proteases and tandem mass spectrometry

Abstract: BackgroundWheat flour is one of the world's major food ingredients, in part because of the unique end-use qualities conferred by the abundant glutamine- and proline-rich gluten proteins. Many wheat flour proteins also present dietary problems for consumers with celiac disease or wheat allergies. Despite the importance of these proteins it has been particularly challenging to use MS/MS to distinguish the many proteins in a flour sample and relate them to gene sequences.ResultsGrain from the extensively characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
301
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(318 citation statements)
references
References 83 publications
(161 reference statements)
16
301
1
Order By: Relevance
“…Analysis of sequence coverage indicated that these spots were produced by cleavage of the N-termini of these proteins. These results are consistent with previous investigations indicating that globulin-3 family proteins can be processed at internal cleavage sites to yield polypeptides with a large range of molecular weights and pI values (Singh et al 2001;Dupont et al 2011;Koziol et al 2012). Interestingly, the spots corresponding to full-length globulin were downaccumulated under e[CO 2 ], whereas those corresponding to endo-proteolytic events accumulated or appeared in samples grown under these conditions.…”
Section: Changes In Seed Proteome Profilessupporting
confidence: 92%
“…Analysis of sequence coverage indicated that these spots were produced by cleavage of the N-termini of these proteins. These results are consistent with previous investigations indicating that globulin-3 family proteins can be processed at internal cleavage sites to yield polypeptides with a large range of molecular weights and pI values (Singh et al 2001;Dupont et al 2011;Koziol et al 2012). Interestingly, the spots corresponding to full-length globulin were downaccumulated under e[CO 2 ], whereas those corresponding to endo-proteolytic events accumulated or appeared in samples grown under these conditions.…”
Section: Changes In Seed Proteome Profilessupporting
confidence: 92%
“…Proteins in breads and sourdough were extracted following the procedure of Dupont et al [15] and separated under non- . Na and K were analysed by inductively coupled plasma atomic emission spectroscopy (ICP-AES) using a Perkin-Elmer Optima 7300-DV spectrophotometer (Waltham MA, USA), following microwave digestion of the samples with nitric acid and hydrogen peroxide.…”
Section: Sodium Docecyl Sulphate Polyacrilamide Gel Electrophoresis (mentioning
confidence: 99%
“…Finally, activity could be recovered in a non-gluten fraction that was present in standard gliadin and that was identified as the family of amylase trypsin inhibitors (ATIs) [15]. ATIs represents ∼2-4% of total wheat protein (as compared to ∼80-90% for gluten) [16]. …”
Section: Introductionmentioning
confidence: 99%